2010
DOI: 10.1007/s10584-010-9982-7
|View full text |Cite
|
Sign up to set email alerts
|

Past connections and present similarities in slave ownership and fossil fuel usage

Abstract: The first part of the paper demonstrates the connection between the abolition of slavery and the Industrial Revolution: steam power changed the perception of labour; new techniques facilitated diffusion of pro-abolition pamphlets; fewer threats to basic existence resulting from industrial advances fostered sensibilities and moral standards toward abolitionism; and, through industrial development, the North grasped victory in the American Civil War. The second part presents similarities between societies in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…The HANDY study (Motesharrei, Rivas & Kalnay, 2014) identified collapses in our history precipitated by factors such as population decline, economic, intellectual and literacy decline, and political dynamics. The two underlying causes were resource depletion and the economic stratification of society (Mouhot, 2011). Those collapses were localised, or regionalised.…”
Section: Historical Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The HANDY study (Motesharrei, Rivas & Kalnay, 2014) identified collapses in our history precipitated by factors such as population decline, economic, intellectual and literacy decline, and political dynamics. The two underlying causes were resource depletion and the economic stratification of society (Mouhot, 2011). Those collapses were localised, or regionalised.…”
Section: Historical Responsesmentioning
confidence: 99%
“…Green (2018) illustrates change dynamics with the movement to abolish slavery in the 18 th and 19 th centuries, providing an encouraging example of how people extended empathy across racial and geographic boundaries, and abandoning the concept or need for slaves as a cheap human energy source (Rifkin, 2016). The emerging industrial revolution provided a new alternate energy source and aided that transition, including powering the printing of pro-abolition pamphlets (Mouhot, 2011).…”
mentioning
confidence: 99%
“…Robert Jay Lifton, en su obra The Climate Swerve (El viraje del clima [2017]) señala que la última vez que un recurso de tal magnitud fue abandonado y no explotado, ocurrió en 1865, cuando los recursos eran seres humanos. La esclavitud generaba más de la mitad de la economía sureña en los Estados Unidos y más del 16 por ciento de la economía del país; lo que es equivalente a unos 10 trillones de dólares estadounidenses (véase también Mouhot, 2011;Hayes, 2014). Fue sencillamente extraordinario que el movimiento abolicionista prevaleciera a pesar de los grandes intereses económicos, que al momento parecían insuperables.…”
Section: La Contaminación Y El Deterioro Ambientalunclassified
“…The obvious answer lies with the fossil fuel industry, which would need to surrender about $20 trillion in untapped wealth for the planet to avoid a temperature increase of two degrees. Robert Jay Lifton argues in The Climate Swerve (2017) that the last time assets like this existed and were stranded was in 1865, when the "assets" took the form of human beings-slaves made up to half of the economy of the Southern United States and 16% of the economy of the entire country, equivalent to about $10 trillion (see also Mouhot, 2011;Hayes, 2014). It was fortunate, then, that the abolitionist movement prevailed at that time despite seemingly insurmountable economic interests.…”
Section: Pollution and Environmental Degradationmentioning
confidence: 99%